English Teacher Strategies in Developing Effective Lesson Plan on Improving Student English Competence - Fadli Wildan Naufal; Rahma Ilyas; Titin Kustini (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
In the ever-evolving landscape of education, the importance of effective lesson planning cannot be overstated. As the cornerstone of successful teaching and learning, lesson plans serve as the roadmap that guides educators through the complex process of imparting knowledge and skills to their students. This study aims to delve into the intricacies of lesson planning, with a particular focus on strategies for creating effective lesson plans, the steps involved in their development, and methods to enhance students' English competence. This research is using qualitative research method by using interview, observation, and collecting lesson plan from english teacher. The setting for this research study is in junior high school. The Research participants is student of junior high school 2 ligung for grade 7 and 8. This research is using observation, interview, and collecting lesson plan from teacher as research instrument. From the researcher analysis English teacher strategy to effective lesson plan is first the teacher must see the condition of the class and the condition of the child and choose simple and fun material. and determine the title of the material to be taught and required time allocation. On making lesson plan teacher can determine the material that want to be taught and then write time allocation for the lesson plan and decide what class and school to be written in lesson plan. Then teacher can write learning objectives learning outcomes and assessment of learning outcomes.